2005
DOI: 10.1111/j.1572-0241.2005.50084.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Gene Polymorphisms and Gastric Cancer Risk in a High-Risk Italian Population

Abstract: Our results suggest that host genetic factors (such as the IL1RN and the IL1B-31 polymorphisms) interact in the complex process of gastric carcinogenesis in this high-risk Italian population. Overall, this effect appears more modest than previously reported in other populations, supporting the hypothesis that other still-to-be-defined factors are important in gastric carcinogenesis. These findings might be due to a haplotype effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 34 publications
4
53
0
6
Order By: Relevance
“…Of the remaining 38 publications, three were eliminated, due to reporting duplicate data 17, 18, 19. Ultimately, 37 studies from 35 publications 6, 10, 14, 15, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 including 6108 cases and 8980 controls were included in the meta‐analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 38 publications, three were eliminated, due to reporting duplicate data 17, 18, 19. Ultimately, 37 studies from 35 publications 6, 10, 14, 15, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50 including 6108 cases and 8980 controls were included in the meta‐analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Portuguese and Japanese investigators also showed a strong association between proinflammatory polymorphisms in the IL-1β gene cluster and an increased risk of developing gastric cancer (64,65). An increased risk for gastric cancer associated with proinflammatory IL-1β polymorphisms has now been confirmed in many populations throughout the world (60,65,66). Later studies also determined genetic polymorphisms in TNF-a and IL-10, which, when combined with proinflammatory IL-1β gene cluster polymorphisms, result in a high-risk genotype with a 27-fold or greater risk of developing gastric cancer (67).…”
Section: Host Factors That Affect the Development Of Gastric Cancer Gmentioning
confidence: 98%
“…For IL1B-511, IL1B-31, and IL1RN (analyzed as biallelic loci) polymorphisms, the following algorithm (43) was used to determine the most appropriate genetic model: 25) conducted in Asian populations had cells with no counts, we added 1 for each cell for these studies to determine the genetic model. However, based on the reported increased gastric cancer risk of IL1RN*2 subjects (6,28,36), a dominant genetic model was also considered.…”
Section: Discussionmentioning
confidence: 99%